2023
DOI: 10.1002/jso.27195
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the same‐day discharge following mastectomy before, during and after COVID‐19 pandemic

Abstract: Background and Objectives The majority of patients undergoing mastectomy before the COVID‐19 pandemic were admitted for 23‐h observation to the hospital. Indications for observation included drain care education, pain control and observation for possible early surgical complications. This study compared the rates of outpatient mastectomy before, during, and after the COVID‐19 pandemic and indirectly evaluated the safety of same‐day discharge. Methods We retrospectively analyzed patients undergoing mastectomy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… 21 A recent study published in January 2023 looked at outcomes of same-day discharge mastectomy pre- and post-COVID19 pandemic and showed no difference in complication rates including hematomas, readmissions or surgical site infections. 20 These studies support the continued effort of enhanced recovery after surgery practices which will likely continue to grow in both the number and types of procedures that will be performed as an outpatient.…”
Section: Impact On Breast Cancer Treatmentmentioning
confidence: 60%
See 1 more Smart Citation
“… 21 A recent study published in January 2023 looked at outcomes of same-day discharge mastectomy pre- and post-COVID19 pandemic and showed no difference in complication rates including hematomas, readmissions or surgical site infections. 20 These studies support the continued effort of enhanced recovery after surgery practices which will likely continue to grow in both the number and types of procedures that will be performed as an outpatient.…”
Section: Impact On Breast Cancer Treatmentmentioning
confidence: 60%
“…Given the focus on minimizing exposure of patients and healthcare workers to the virus and shortage of PPE many centers shifted from routine 23-hour observation or admission of patients after mastectomy to same day discharge. 20 This was not only for patients undergoing total mastectomy but also those that underwent mastectomy with immediate reconstruction. Although the COVID-19 pandemic placed unprecedented emphasis on outpatient breast cancer surgery, the initial shift to home recovery after mastectomy began in the early 2000s with literature supporting that home recovery is a safe option for appropriately selected patients without increased risk of complications.…”
Section: Impact On Breast Cancer Treatmentmentioning
confidence: 99%
“…In addition, we included a cohort of patients who were mainly recovering or fully recovered from COVID-19 and undergoing elective oncologic resections at a high-volume comprehensive cancer center which may not be representative or generalizable across all settings. Although a recent study reported that the rate of postoperative complications is not increased in patients undergoing mastectomy in the ambulatory setting, our results cannot be generalized to oncological patients undergoing same-day surgery [ 39 ]. Second, we excluded patients undergoing emergency surgery or those with an active infection whose risk of postoperative delirium could have been higher than those recovering from the disease [ 40 ].…”
Section: Discussionmentioning
confidence: 87%
“…A comprehensive systematic review of these changes was conducted by Hemal and colleagues, who found a temporary reduction in autologous reconstruction, increased use of DTI over TE‐based reconstruction, emphasis on expedited discharge postoperatively, and no significant increase in complications 12 . Indeed, a comparison of protocols before, during, and after the COVID‐19 pandemic among 357 patients done by Olimpiadi et al revealed a tripling of outpatient mastectomies and increased use of pectoralis muscle blocks 13 . Among alloplastic reconstruction in particular, COVID‐19 prompted an increase in delayed reconstruction and increased outpatient surgeries 14 …”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 5 Indications for admission among Group 2b. 13 Among alloplastic reconstruction in particular, COVID-19 prompted an increase in delayed reconstruction and increased outpatient surgeries. 14 Analysis of complications and outcomes among smaller patient cohorts showed no difference between patients who underwent same-day surgery versus those admitted for observation, [15][16][17][18] which has been supported by aggregate data from larger databases and systematic reviews.…”
Section: F I G U R E 1 Flow Diagram Of Group Divisions Of Included Pa...mentioning
confidence: 99%